Polyhalides as efficient and mild oxidants for oxidative carbene organocatalysis by radical processes - Wu, Xingxing (2017)
Simple and inexpensive polyhalides (CCl4 and C2Cl6 ) have been found to be effective and versatile oxidants in removing electrons from Breslow intermediates under N-heterocyclic carbene (NHC) catalysis. This oxidative reaction involves multiple single-electron-transfer (SET) processes and several radical intermediates. The α, β, and γ-carbon atoms of aldehydes and enals could be readily functionalized. Given the low cost of the oxidants and the broad applicability of the reactions, this study is expected to greatly enhance the feasibility of oxidative NHC catalysis for large-scale applications. Also this new SET radical process with polyhalides as single-electron oxidants will open a new avenue in the development of NHC-catalyzed radical reactions.